Application of mindfulness therapy in reducing depression levels in the elderly - Ginanjar, Yoga; Nurhayati, Nurhayati; Anggraini, Dewi; Khasanah, Uswatul; Anwar, Syamsul; Rahman, Irpan Ali (Science Midwifery, 2024)
The elderly population is part of family members and community members who are increasing in number in line with the increase in life expectancy, the elderly are also one of the vulnerable groups that need serious treatment because naturally the elderly experience a decline both in terms of physical, biological and mental. One of the health disorders that can appear in the elderly is mental disorders. The mental disorder that often appears during this period is depression, the highest prevalence of depression in Indonesia is experienced by the population aged 75 years at 8.9%, 65-75 years at 0%, and 55-64 years at 6.5%, the purpose of this study is to look at the effect of mindfulness on reducing the rate of depression in the elderly. The Evidence Base Nursing (EBNP) practice method is carried out in Linggasari District, Ciamis Regency. The number of respondents was 33 respondents, in eight weeks the respondents were given intervention therapy in groups with a vulnerable time of 1-2 hours. Based on the results of the normality test using Saphiro Wilk and Kolmogorov showed that the data were normally distributed (p>significance value 0.05), so that the statistical test on the difference between pre-intervention and post-intervention was carried out using the Paired t-Test. The results of the statistical test can be explained that there is a significant difference between the screening results of the first depression level measurement and the second pre and post screening after mindfulness is carried out and a p-value of 0.000 (P<0.05) is obtained.